Artificial Intelligence in IoT - Al-Turjman, Fadi.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book provides an insight into IoT intelligence in terms of applications and algorithmic challenges. The book is dedicated to addressing the major challenges in realizing the artificial intelligence in IoT-based applications including challenges that vary from cost and energy efficiency to availability to service quality in multidisciplinary fashion. The aim of this book is hence to focus on both the algorithmic and practical parts of the artificial intelligence approaches in IoT applications that are enabled and supported by wireless sensor networks and cellular networks. Targeted readers are from varying disciplines who are interested in implementing the smart planet/environments vision via intelligent wireless/wired enabling technologies. Includes the most up-to-date research and applications related to IoT artificial intelligence (AI); Provides new and innovative operational ideas regarding the IoT artificial intelligence that help advance the telecommunications industry; Presents AI challenges facing the IoT scientists and provides potential ways to solve them in critical daily life issues.
Chapter1: A Systematic Review of the Convergence of Augmented Reality, Intelligent Virtual Agents, and the Internet of Things -- Chapter2: Improving the Physical Layer Security in IoT-5G Systems -- Chapter3: Emotional ANN (EANN): A New Generation of Neural Networks for Hydrological Modeling in IoT -- Chapter4: Smart Tourism Destination in Smart-cities Paradigm: A Model for Antalya -- Chapter5: A Hybrid approach for image segmentation in the IoT Era -- Chapter6: Big Data Analytics for Intelligent Internet of Things -- Chapter7: Blockchain and Internet of Things-Based Technologies for Intelligent Water Management System -- Chapter8: Digital Forensics for Frame Rate Up-Conversion in Wireless Sensor Network -- Chapter9: A Neuro Fuzzy Based Multi Criteria Risk Evaluation Approach: A Case Study of Underground Mining -- Chapter10:Intelligent IoT Communication in Smart Environments: An Overview.
Keywords: Telecommunication; Application software; Electronics; User interfaces (Computer systems).; Human-computer interaction; Communications Engineering, Networks; Computer and Information Systems Applications; Electronics and Microelectronics, Instrumentation; User Interfaces and Human Computer Interaction